2020
DOI: 10.1021/acs.est.0c05537
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable Environmental Pollutant Patterns in Sediments from Passive Equilibrium Sampling

Abstract: Sediment-associated risks depend on the bioavailable fraction of organic chemicals and cannot be comprehended by their total concentrations. The present study investigated contamination patterns of bioavailable chemicals in sediments from various sites around the globe by using passive equilibrium sampling. The extracts had been characterized previously for mixture effects by in vitro reporter gene assays and were in this study analyzed using gas chromatography-high resolution mass spectrometry for 121 chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…They compared the bioassay results with chemical analysis and indicated that the detected chemicals could not entirely explain the effects detected with the bioassays. Two more recent studies evaluated Chinese sediments (Niu et al, 2020) and world-wide sampled sediments (Jahnke et al, 2018;Muz et al, 2020) using both total accelerated solvent extraction and PDMS and confirmed that typically less than 10% of the effects and BEQ were bioavailable (Table 15.1).…”
Section: Sedimentsmentioning
confidence: 90%
See 2 more Smart Citations
“…They compared the bioassay results with chemical analysis and indicated that the detected chemicals could not entirely explain the effects detected with the bioassays. Two more recent studies evaluated Chinese sediments (Niu et al, 2020) and world-wide sampled sediments (Jahnke et al, 2018;Muz et al, 2020) using both total accelerated solvent extraction and PDMS and confirmed that typically less than 10% of the effects and BEQ were bioavailable (Table 15.1).…”
Section: Sedimentsmentioning
confidence: 90%
“…The same bioassays can be applied and a lot of the developments with respect of mapping chemicals to modes of action and toxicity pathways and mixture effects modelling can be directly translated to these other matrices. Iceberg modelling, for instance, has already been applied to sediments (Muz et al, 2020;Niu et al, 2020) and to biota samples (Jin et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been considerable recent interest and work on CA and other mixture modeling approaches, particularly in the context of in vitro assays and whole-mixture testing. For instance, several studies have found that effects of bioavailable extracts from contaminated sediments are consistent with CA or a model combining CA and independent action [ 15 , 16 , 17 ]. Additionally, both non-targeted and effect-directed approaches have been proposed to identify components within mixtures [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that sediments may act as a repository for a variety of contaminants including radionuclides (Durrant et al, 2018;Knies et al, 2006;Muz et al, 2020;Zaborska et al, 2011). Sediments with high content of clay minerals (e.g.…”
Section: Introductionmentioning
confidence: 99%